2018
DOI: 10.1177/2515690x18768727
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Hypoglycemic Effect of Kigelia africana (Lam): Studies With Alloxan-Induced Diabetic Mice

Abstract: The claims by the traditional herbal medicine practitioners that Kigelia africana has bioactivity against several diseases, including diabetes mellitus, were investigated in this study. Type I diabetes mellitus was induced in mice by intraperitoneal administration of alloxan monohydrate followed by treatment with the therapeutic doses of the aqueous and ethyl acetate leaf extract of K africana to the experimentally diabetic mice. The treatment effects were compared with the normal control, diabetic control, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…An important finding from this meta-analysis is the dose independence of HA extract to its observed glucose-lowering effect, that was not apparent from results of individual studies. However, this is not an uncommon observation, as dose independence of pharmacological effects of plant extracts were reported in studies with Musa AAA fruit (30), leaf extracts of K. Africana(31) and Camellia sinensis green tea extract(32). Possible explanation for this dose independent behaviour of HA extract could be the saturation of active transport of phytochemicals to cells in 100 – 600 mg/kg dose range with the excess amount getting excreted(33).…”
Section: Discussionmentioning
confidence: 96%
“…An important finding from this meta-analysis is the dose independence of HA extract to its observed glucose-lowering effect, that was not apparent from results of individual studies. However, this is not an uncommon observation, as dose independence of pharmacological effects of plant extracts were reported in studies with Musa AAA fruit (30), leaf extracts of K. Africana(31) and Camellia sinensis green tea extract(32). Possible explanation for this dose independent behaviour of HA extract could be the saturation of active transport of phytochemicals to cells in 100 – 600 mg/kg dose range with the excess amount getting excreted(33).…”
Section: Discussionmentioning
confidence: 96%
“…Bark decoction Laxative [27] Ash leaves mixed with honey High blood pressure [22] Fruits Mature fruit is used for treating wounds, abscesses, dressing wounds, skin cancer, reducing breast metastasis, ulcers, syphilis, rheumatism, fungal infections, boils, psoriasis, leprosy, venereal diseases and acne [3,14,22,23,27,35,42] Leaves Malaria, rheumatism, wounds, ulcers, retained placenta, venereal diseases and diarrhea [43] Fruit and bark (lesser extent) extracts Dysentery, hemorrhoids, constipation, wounds, ulcers, boils, abscesses, rheumatism, syphilis and gonorrhea [30,33] Fruit and root decoction…”
Section: Fruitsmentioning
confidence: 99%
“…The authors diluted and tested the plant extracts across a concentration range of doses 5 mg/mL to 0.1 mg/mL, which increases the reliability of the results. The iridoids specioside and verminoside in K. africana are responsible for its antibacterial effects [42].…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches documented the use of Kigelia africana in the treatment of diabetes as an antidiabetic agent in animal models. [ 29,30 ] In addition, the pharmaceutical abilities of K. africana have been recognized and have witnessed a surge in research interest to even include being used as an antidiabetic agent. Akunyili and Houghton (1991) reported that the ethnomedicinal stem bark of K. africana is used in the treatment of diabetes.…”
Section: Introductionmentioning
confidence: 99%